Suomalaiset sivulliset Eksistentiaalisten tunteiden kertominen 1950-luvun proosassa - Nykänen, Elise (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2022)
This study explores the narration of existential feelings, or feelings of being in the world, in post-war Finnish prose fiction. The book presents five case studies which address modern individuals' struggles in boundary situations of their lives. Rigorous readings of the works of Kerttu-Kaarina Suosalmi, Lassi Nummi, Marko Tapio, Tyyne Saastamoinen and Eeva-Liisa Manner all show the influence of French existentialism and its predecessors on post-war Finnish modernism for the first time in literary studies. The outsider figures and their experiences of the absurd, which have enticed the cultural imagination since ancient cults and the Book of Job, connect to the atmosphere of shared melancholy in post-war Finnish culture and society. The study participates in the rich contemporary debates on the effects of literature by focusing on less-discussed aspects of bodily feeling, affect, emotion and mood in late Finnish modernism. The book's methodological contribution to narrative theory is that it combines a phenomenological analysis of reading with a rhetorical theory of narrative and politically informed, multidisciplinary emotion studies. The five case studies show how modernist outsider prose fiction in Finland resorts to irony, metafiction, allegory and the imaginative to generate ethically challenging narrative tension and an ambivalence of negative and positive emotion in readers. The opposing impulses of the aesthetic response produce an openness of interpretation. This openness provides us with the possibility of a more complex cultural understanding of emotion and ethics in the lives of strangers within literature and outside it.